1999
DOI: 10.1007/s002689900619
|View full text |Cite
|
Sign up to set email alerts
|

New Simple Technique for Hepatic Parenchymal Resection Using a Cavitron Ultrasonic Surgical Aspirator® and Bipolar Cautery Equipped with a Channel for Water Dripping

Abstract: We have developed a new technique to resect hepatic parenchyma without inflow occlusion by using the Cavitron Ultrasonic Surgical Aspirator (CUSA) and bipolar cautery with a saline irrigation system. The significance of this method in hepatectomy was analyzed in comparison with historical control of hepatectomy using Pringle's maneuver. An ordinary bipolar cautery was remodeled with an infusion line to bring saline droplets down the inner surface of one arm of the tweezers through an opening about 1.5 cm proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 4 publications
1
88
0
5
Order By: Relevance
“…Takasaki et al [32] proposed that rem K ICG > 0.062 is a safety threshold for postoperative mortality [32]. Other investigators also reported that postoperative morbidity was low in patients with rem K ICG > 0.06 after a major hepatectomy [46], or that rem K ICG 0.05 was a threshold for survival in patients with bile duct cancer who underwent preoperative PVE [47]. More recently, on the basis of statistical analysis, a rem K ICG of 0.05 has been again reported as a useful cut-off value for predicting mortality and morbidity in patients with biliary cancer [48,49].…”
Section: Pdr Icg or K Icgmentioning
confidence: 99%
“…Takasaki et al [32] proposed that rem K ICG > 0.062 is a safety threshold for postoperative mortality [32]. Other investigators also reported that postoperative morbidity was low in patients with rem K ICG > 0.06 after a major hepatectomy [46], or that rem K ICG 0.05 was a threshold for survival in patients with bile duct cancer who underwent preoperative PVE [47]. More recently, on the basis of statistical analysis, a rem K ICG of 0.05 has been again reported as a useful cut-off value for predicting mortality and morbidity in patients with biliary cancer [48,49].…”
Section: Pdr Icg or K Icgmentioning
confidence: 99%
“…Hepatic parenchymal dissection was performed using an ultrasonic surgical aspirator and bipolar irrigation forceps [16] . Tumor thrombi confined to the first branch of the portal vein were resected with the liver.…”
Section: Hepatic Resection Techniquementioning
confidence: 99%
“…Advances in technology have elaborated the techniques for parenchymal transection during hepatectomy from the classic clamp crushing technique [18] to a combination of various sophisticated devices [19,20,21]. …”
Section: Discussionmentioning
confidence: 99%